The Community of Steinkopf : an stenographic study and an analysis of social °hangs in Namaqualand - Carstens, WP (African Studies, 2014)
This thesis consists mainly of an analysis of the social structure of a small community of rural Coloured people who live on a reserve surrounding the old mission station, Steinkopf, in the North-Western Cape Province. It has been written primarily as an ethnographic study of one of the constituent communities of a composite society, the Republic of South Africa, although a chapter has been devoted to the comparison of Steinkopf with the four other reserves in the Namaqualand district. I have attempted also to desscribe and analyse certain of the processes of social change in the North-Western Cape with particular reference to these Coloured Reserves.